Music and religious change among progressive Jews in London : being liberal and doing traditional - Illman, Ruth (Lexington Books, 2018)
This book analyses the role of music in processes of religious change in contemporary progressive Judaism. Based on ethnographic research conducted in London, it illustrates a growing trend among progressive Jews in the West today: the desire to combine liberal theology with forms of practice experienced as more traditional.